Performance comparison of a building-integrated photovoltaics (BIPV) module with patterned glass in Korean weather - Ji Woo Sohn; Hongjun Jang; Young-Su Kim; Donghwan Kim; Sungho Hwang; Yoonmook Kang (Journal of Power Sources Advances)
In the photovoltaic (PV) industry, building-integrated photovoltaics (BIPV) are promising products for zero-energy buildings that offer solutions to the issue of limited space in urban areas. BIPV modules offer not only power production but also significant visual appeal. This study aims to assess the aesthetic qualities of BIPV using patterned glass. We evaluate the energy yield of BIPV performance compared with conventional modules in a vertically oriented south-facing system under Korean weather conditions. Product characteristics such as the external quantum efficiency (EQE) spectrum, cell-to-module (CTM) conversion ratio, and power under tilted light conditions are analyzed. Unlike previous studies that report lower energy yields in BIPV systems, this BIPV module with patterned glass exhibits only a 0.5 % reduction in energy yield because of the lower open-circuit voltage (Voc) caused by the thicker glass (5 mm) compared to the reference glass (3.2 mm). In contrast, the short-circuit current (Isc) in the field is higher, likely due to the morphology of the patterned glass and the tilted incident light under Korean summer conditions. This result suggests BIPV modules using patterned glass are viable candidates for aesthetically pleasing, south-facing, and vertical systems in zero-energy buildings.